Child Protection and Cross‐Sector Practice: An Analysis of Child Death Reviews to Inform Practice When Multiple Parental Risk Factors Are Present. (March 2014) - Frederico, Margarita; Jackson, Annette; Dwyer, Jenny
<x xml:space="preserve">Abstract</x> This paper draws upon the findings of an analysis of 16 child death reviews of children known to child protection services in Victoria, Australia. The purpose of the research was to assist in understanding the impact on children of the coexistence of the parental risk factors of mental health problems, family violence and substance abuse. The common coexistence of the three risk factors was identified by the Victorian Child Death Review Committee in its analysis of child death reviews conducted by the Office of the Child Safety Commissioner. The researchers analysed a group of review reports and interviewed and surveyed practitioners in a range of fields. Lessons from filicide research have been integrated into the findings identifying lessons for policy and practice, and the importance of multi‐service collaboration. A framework for understanding different elements of sharing knowledge is presented. Copyright © 2014 John Wiley & Sons, Ltd. <boxed-text content-type="pullQuote" id="car2321-blk-0001" position="anchor" orientation="portrait"> understanding the impact on children of the coexistence of the parental risk factors of mental health problems, family violence and substance abuse </boxed-text> Key Practitioner Messages Research on filicide and child death reviews can contribute to understanding risk to children and informing practice. The need to pay increased attention when parental substance abuse, mental health problems and family violence coexist. A gender analysis contributes to understanding families and informing systems responses. A multi‐service collaborative framework can support sharing of knowledge when parental risk factors coexist. <boxed-text content-type="pullQuote" id="car2321-blk-0002" position="anchor" orientation="portrait"> A multi‐service collaborative framework can support sharing of knowledge when parental risk factors coexist </boxed-text>